The effect of starvation on chemical composition of Common carp Cyprinus carpio L. - Al-Hamadany, Qusay Hamid (Iraqi Journal of Aquaculture, 2022)
The experiment was conducted using 48 fish, common carp Cyprinus carpio (average weight 41.51 + 3.51 gm), The fish were distributed on 6 aquaria each one contain 8 individuals, after two weeks acclimatization on commercial diet (35% protein) to reduce individual differences in nutritional status, fish were exposed to starvation, fish weighed and body composition (moisture, protein, lipid and ash) was analyzed using 5 specimens every two weeks. Fish weight decreased noticeably as a result of consumption of some components of the body to sustain essential activities, fish showed significant decrease (P < 0.01) in carcass dry matter, protein and lipid, while moisture increased significantly (P < 0.01), fish used 91.8% of carcass lipid and 20.1% of carcass protein during the experiment period, no significant (P > 0.05) effect of starvation on carcass ash except the last two weeks of experiment.